Chemically exfoliated nanosheets of β-Bi2O3. (1st October 2022) - Hoff, Brianna L; Cheng, Guangming; Villalpando, Graciela; Yuan, Fang; Yao, Nan; Schoop, Leslie M
Abstract: Exploring two dimensional (2D) materials is important for further developing the field of quantum materials. However, progress in 2D material development is limited by difficulties with their production. Specifically, freestanding 2D materials with bulk non-layered structures remain particularly challenging to prepare. Traditionally, chemical or mechanical exfoliation is employed for obtaining freestanding 2D materials, but these methods typically require layered starting materials. Here we put forth a method for obtaining thin layers of β -Bi2 O3, which has a three-dimensional covalent structure, by using chemical exfoliation. In this research, Na3 Ni2 BiO6 was exfoliated with acid and water to obtain β -Bi2 O3 nanosheets less than 10 nm in height and over 1 µ m in lateral size. Our results open the possibility for further exploring β -Bi2 O3 nanosheets to determine whether their properties change from the bulk to the nanoscale. Furthermore, this research may facilitate further progress in obtaining nanosheets of non-layered bulk materials using chemical exfoliation.